PTU-184 Unload the Burden of Unnecessary Investigations and Reduce the Delay in Diagnosing Bile Acid Malabsorption (BAM). (4th June 2013) - Kok, B; Malhotra, R; Mistry, A; Burdsall, J; Milestone, A; Ransford, R
Abstract : Introduction: BAM is an often forgotten cause for chronic diarrhoea and though it is easily diagnosed by means of the SeHCAT scan, the diagnosis is often made late in the day with SeHCAT used only as a third or fourth line investigation. In this observational study we aim to analyse the unnecessary investigations and chronological delay it took to diagnose BAM in our centre. Methods: All patients who underwent a SeHCAT scan between the period January 2009-June 2012 were identified. Patient notes were retrieved and blood results, radiological imaging and endoscopy procedures performed prior to SeHCAT scan were reviewed. An abnormal SeHCAT was defined by bile acid retention < 8%. Results: A total of 112 patients underwent a SeHCAT scan during this period. 4 patients were excluded due to unavailability of notes. 53 patients (49%) had abnormal SeHCAT results. All 53 patients had normal inflammatory markers (normal white cell count, C reactive protein < 5), 98% (52) had normal haemoglobin levels and 91% (48) had coeliac disease excluded by negative tissue transglutaminase antibodies. The median age at time of diagnosis was 52 years (range 26–80 years), 38 of the 53 patients being female. The average stool frequency was 7 times a day. In these 53 patients, a total of 5 hydrogen breath tests were performed prior to SeHCAT, 4 of them normal. A total of 19 barium studies were performed prior to SeHCAT, 15 were normal. A total of 18 CT Abdomen/Pelvis were performed prior to SeHCAT, 13 were normal. A total of 21 flexible sigmoidoscopies were performed, all of them normal. A total of 24 colonoscopies were performed, 21 of them normal. All abnormal results from the above summary apart from 2 abnormal CT Abdomens (which were detected in patients who were post-cholecystectomy) were found in patients who were known to be at risk of Type I BAM (previous TI Crohn's disease/previous ileal resection/previous pelvic radiotherapy). This includes the 3 abnormal colonoscopies from patients with known Crohn's disease with histology confirming active Crohn's inflammation. The average time from first clinic consultation to time of diagnosis was 4.8 months (range 2 – 34 months). Conclusion: There is a significant time delay in diagnosing BAM and the study confirmed our suspicions that patients with BAM often undergo a whole barrage of investigations which yield negative results. Patients with Type I BAM, however, seem to yield abnormalities in most other investigations which might throw physicians off course initially, resulting in further diagnostic delay. BAM certainly needs to be thought of earlier in all patients and it merits a consideration even in patients who appear to have active inflammatory disease. Disclosure of Interest: None Declared.